How to scale the voluntary carbon credit market effectively to motivate investment in climate-action projects?- a qualitative qnalysis of structural barriers to growth and development of a strategic roadmap for market success - Votsmeier, Tobias (2022)
Voluntary carbon markets have promised an impactful contribution toward climate change mitigation efforts for more than a decade. Yet, there is a severe discrepancy between the theoretical potential and the factual impact of voluntary carbon markets. Existing literature identified structural barriers to market growth but failed to develop effective solutions that enable market scaling. Based on the three dimensions of challenges, governance, lack of market infrastructure, and limited use of technology, this study develops six tangible initiatives as part of a strategic roadmap to enable the market to scale effectively.